Correction: New synthesis of phenyl-isothiocyanate C-functionalised cyclams. Bioconjugation and 64Cu phenotypic PET imaging studies of multiple myeloma with the te2a derivative. Issue 15 (23rd March 2016) - Halime, Zakaria; Frindel, Mathieu; Camus, Nathalie; Orain, Pierre-Yves; Lacombe, Marie; Bernardeau, Karine; Chérel, Michel; Gestin, Jean-François; Faivre-Chauvet, Alain; Tripier, Raphaël
Abstract : Correction for 'New synthesis of phenyl-isothiocyanate C -functionalised cyclams. Bioconjugation and 64 Cu phenotypic PET imaging studies of multiple myeloma with the te2a derivative' by Zakaria Halime et al., Org. Biomol. Chem., 2015, 13, 11302–11314.